Kisspeptin and Leptin as Treatments for Functional Hypothalamic Ammenorhea (FHA): Experimental Approach or Emerging Therapy? - Bednarczyk, Malgorzata; Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra (Quality in Sport, 2026)
Functional hypothalamic amenorrhea (FHA) is a common cause of amenorrhea among women in reproductive age. The disturbance is often associated with stress and deficiency in energy availability caused by either intensive exercise or improper nutrition. Those factor affect the hypothalamic-pituitary-gonadal axis and further absence of ovulation and normal menstrual cycle. Treatment should be directed to treatment of the etiology, however sometimes it is not enough. For this reason, novel therapies emerged to counteract the consequences of FHA to support restoring that lifestyle changes are not capable of. This review summarizes current knowledge on the leptin and kisspeptin treatment, which recently gained more interest, due to it physiological basis in hypothalamic-pituitary-gonadal axis. Furthermore, paper evaluates clinical data, its limitations and safety consideration, and more importantly, the need for future research.